Homoconjugation enhances the photophysical and electrochemical properties of a new 3D intramolecular charge transfer iptycene displaying deep blue emission. Issue 41 (13th September 2019) - Montanaro, Stephanie; Congrave, Daniel G.; Etherington, Marc K.; Wright, Iain A.
Abstract : Greater than the sum of its parts – a 3D ICT molecule displays greatly improved optoelectronic properties over a 2D analogue. Abstract : A new structural class of 3D molecule capable of intramolecular charge transfer (ICT) is introduced, based upon an electron poor ring-fused triptycene core. Its photophysical and electrochemical properties are evaluated in comparison with an analogous molecule, representative of a single fin of the iptycene. Homoconjugation through the delocalised LUMO of the iptycene facilitates a great increase in transition probability both to and from the ICT state, while the deep blue photoluminescence of the single fin is retained. The peripherally distributed HOMO of the iptycene also permits reversible access to a tricationic state in a single step and at an oxidation potential lower than that of the single fin. This first example demonstrates great potential for this 3D design concept in producing new optoelectronic molecular materials.